Galicia’s Escape from the Malthusian Trap. A Long and Short-Term Analysis of the Demographic Response to Economic Conditions in the Population of Galicia 1819–1913 - Ogórek, Bartosz (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
Galicia’s escape from the Malthusian trap. A long and short-term analysis of demographic response to the economic conditions in the population of Galicia 1819–1913 (Summary) The purpose of the article is to analyze Malthusian mechanisms to be found in operation in the population of Galicia in the years 1819–1913. Relying on published sources which record both the condition and the natural movement of the Galician population, as well as price movements in key food staples on the Lwów and Kraków markets, the author has examined the relationship between the population’s economic conditions and demographic trends in the long and short-term. The analysis of the long-term relationships shows that it was not until the last decades of the nineteenth century that Galicia set itself free from Malthusian mechanisms. At that time, the demographic situation began to improve for the fi rst time. The improvement came despite some adverse economic phenomena such as falling wages and rising prices. The author points to a number of causes of this situation: the advancement in agricultural production, mass emigration and some institutional changes. The analysis of short-term relationships shows that the nineteenth-century Galicia – although it was lagging behind the countries of Western Europe in terms of GDP per capita, the percentage of those who were literate, or the industrialization processes – was affected by the operation of Malthusian mechanisms to only a slightly greater extent than the western part of the Old Continent. The comparison of the Galician population’s demographic response to an increase in the staple food prices with the way in which the population of the whole of Austria reacted to this increase justifies the conclusion that, with regard to this response, the inhabitants of Galicia were doing as well as the people inhabiting the whole of Cisleithania. This of course does not mean that living standards in Galicia were similar to those typifying Austria or Western Europe, but it does allow one to contest the opinion that the Galician population was considerably vulnerable/prone to economic crises. In defiance of the myth of “Galician misery”, one can say that there actually existed no positive (that is, those bound up with the death rate) constraints on the growth of the Galician population in the period of autonomy.